Math virtual assistant

Calculators Topics Go Premium About Snapxam
ENGESP

Step-by-step Solution

Derive the function z=ln(x^2+y^2)x=t^2y=t^(-2) with respect to x

Go
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step explanation

Problem to solve:

$\frac{d}{dt}\left(z=\left(\ln\:\left(x^2+y^2\right)\right)x=\left(t^2\right)y=\left(t^{-2}\right)\right)$

Answer

No steps currently available for this problem.
$\frac{d}{dt}\left(z=\left(\ln\:\left(x^2+y^2\right)\right)x=\left(t^2\right)y=\left(t^{-2}\right)\right)$

Main topic:

Differential calculus

Used formulas:

1. See formulas

Time to solve it:

~ 0.82 seconds